2021
DOI: 10.4081/monaldi.2021.1621
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac rehabilitation outcome after transcatheter aortic valve implantation

Abstract: Patients with severe aortic stenosis are increasingly treated with transcatheter aortic valve implantation (TAVI) as a safer option to surgical aortic valve replacement (sAVR).  Similar to many other heart diseases, after the specific therapeutic intervention patients are eligible for cardiac rehabilitation (CR) for the purpose of functional recovery. Thus far, CR after both sAVR and TAVI has been used to a limited extent, as shown by the availability of only two meta-analyses including 5 studies and 6 studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…However, it is a strength that we screened all the patients scheduled for TAVI in our hospital, which was similar to the feasibility randomized study performed by Rogers et al [ 8 ]. Apart from the walked distance, the age of the participants in our study and several clinical features, such as the presence of comorbidities, ejection fraction, and NYHA classification were similar to those in studies investigating the effect of CR following TAVI [ 8 , 51 - 54 ].…”
Section: Discussionsupporting
confidence: 68%
“…However, it is a strength that we screened all the patients scheduled for TAVI in our hospital, which was similar to the feasibility randomized study performed by Rogers et al [ 8 ]. Apart from the walked distance, the age of the participants in our study and several clinical features, such as the presence of comorbidities, ejection fraction, and NYHA classification were similar to those in studies investigating the effect of CR following TAVI [ 8 , 51 - 54 ].…”
Section: Discussionsupporting
confidence: 68%
“…[48] Of note, the walked distance in our cohort at baseline was higher (median 400 m) than the distance reported in studies investigating the effects of CR following TAVI, probably because we assessed 6MWT prior to the surgery, while the assessment in most studies was performed after the surgery. [7,[9][10]15,[49][50][51] Assessing the walked distance after the surgery may be negatively influenced by inactivity or tiredness post-surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Regularly-scheduled exercises, along with other interventions, such as medications, are an established component of CR, and could significantly complement the effects of TAVR. Several studies have shown intensive post-operative recovery regimens, such as short-term exercise-based CR, especially for Phase I during hospitalization, could increase functional capacity, quality of life ( 42 44 ), and exercise tolerance, particularly with respect to the distance in the 6 min walk test (6MWT) ( 18 , 45 ) and maximum workload ( 46 48 ). These effects are coupled with lowered hospitalization lengths ( 49 ), frailty ( 50 ), anxiety, and disability.…”
Section: Cr Use In Tavrmentioning
confidence: 99%